Shadows - McKinley, Robin (Nancy Paulsen Books, an imprint of Penguin Group (USA) Inc., 2013)
"Magic is illegal in Newworld, so Maggie struggles to explain the strange shadows--that only she can see--that seem to accompany her new stepfather everywhere"--